(NmATEMATI^ESKAQ TEORIQ OPTIMALXNYH PROCESSOW (B/s - (NpONTRQGIN(B, (NlEW sEMENOWI^s; (NbOLTQNSKIJ(B, (NwLADIMIR gRIGORXEWI^s; (NgAMKRELIDZE(B, (NrEWAZ wALERIANOWI^s; (NmI]ENKO(B, (NeWGENIJ fROLOWI^s ((NmOSKWA (B:s (NfIZMATGIZ(B,s, 1961)
(NsPISOK LIT(B.: (NS(B. 389 - 391s
Keywords: (NwARIACIONNOE IS^ISLENIEs; (NoPTIMALXNYE PROCESSYs